PERTUMBUHAN DAN PRODUKSI CABAI RAWIT (CAPSICUM FRUTESCENS) PADA SISTEM IRIGASI TETES TERHADAP APLIKASI PAKLOBUTRAZOL DAN PUPUK SILIKA DI KABUPATEN LOMBOK UTARA - JUFRI, AFIFAH FARIDA; NURRACHMAN, NURRACHMAN; JAYAPUTRA, JAYAPUTRA; NUFUS, NOVITA HIDAYATUN; JIHADI, AMRUL (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to determine the effect of the combination of silica and paklobutrazaol on increasing cayenne pepper production. The research was conducted in North Lombok at an altitude of 300 m above sea level with dry, sandy soil conditions. The research was carried out for 7 months, from May to October 2023. The materials used were free-pollen cayenne pepper of the CBR 25 variety, liquid silica, and paclobutrazole. The research design used was a factorial randomized block design (RAK). The first factor is paclobutrazol, which consists of 3 levels of treatment: without paklobutrazol, paclobutrazol 250 ppm, and paclobutrazol 500 ppm. The second factor is silica with two levels, namely without silica and 2 ml/L silica. The results showed that silica application resulted in growth that was not significantly different in plant height, diameter, and canopy width but significantly different in the percentage of flower fall and fruit set per plant. Plants applied with silica gave a smaller percentage of flower fall than without silica at 12.17%, and fruit weight per plant was heavier at 182.75 gr/plant. Giving paclobutrazol to plants gave significantly different results in plant height, stem diameter, crown width, number of flowers, percentage of flower drop, number of fruit, and fruit weight per plant. From the results, it can be seen that the treatment with 500 ppm paclobutrazol gave the highest number of flowers, number of fruits, and fruit weight compared to other treatments. The interaction between silica and paclobutrazol gave results that were not significantly different except for plant height.